The impact of disability on performance in a high-stakes postgraduate surgical examination: a retrospective cohort study. (February 2022) - Ellis, R; Cleland, J; Scrimgeour, DSG; Lee, AJ; Brennan, PA
Objective: Despite rising numbers of doctors in the workforce with disabilities, little is known about the impact of disabilities on postgraduate performance. To ensure all groups are treated fairly in surgical training, it is essential to know whether any attainment differences exist in markers of surgical performance. To address this gap, we assessed the impact of disabilities on performance on the Intercollegiate Membership of the Royal College of Surgeons examination (MRCS). Design: Retrospective cohort study. Setting: Secondary care. Participants: All UK MRCS candidates attempting Part A ( n =  9600) and Part B ( n =  4560) between 2007 and 2017 with linked disability data in the UK Medical Education Database (https://www.ukmed.ac.uk ) were included. Main outcome measures: Chi-square tests and correlation coefficients established univariate associations with MRCS performance, while multiple logistic regressions identified independent predictors of success. Results: Though MRCS Part B pass rates were similar ( p  = 0.339), candidates with registered disabilities had significantly lower first-attempt Part A pass rates (46.3% vs. 59.8%, p  < 0.001). Candidates with disabilities also performed less well in examinations taken throughout school and medical school, and after adjusting for prior academic performance and sociodemographic predictors of success, logistic regression found that candidates with disabilities were no less likely to pass MRCS than their peers (odds ratio 1.04, 95% confidence interval 0.66 to 1.62). No significant variation was found in MRCS performance between type of disability or degree of limitations caused by disability ( p  > 0.05). Conclusion: Although candidates with registered disabilities performed less well in formal, written examinations, our data indicate that they are as likely to pass MRCS at first attempt as their peers who achieved similar grades at high school and medical school. In order to enable equity in career progression, further work is needed to investigate the causes of attainment differences in early career assessments.